Optimum in ligand density for conductivity in polymer electrolytes. Issue 12 (28th September 2021) - Schauser, Nicole S.; Richardson, Peter M.; Nikolaev, Andrei; Cooke, Piper; Kliegle, Gabrielle A.; Susca, Ethan M.; Johnson, Keith; Wang, Hengbin; Read de Alaniz, Javier; Clément, Raphaële; Segalman, Rachel A.
Abstract : Optimization of Li + conductivity relies on a balance between ligand presence and the ability of the chains to rearrange locally to facilitate transport. Abstract : Current design rules for ion conducting polymers suggest that fast segmental dynamics and high solvation site density are important for high performance. In a family of imidazole side chain grafted siloxane polymer electrolytes containing LiTFSI, we conclude that while the presence of imidazole solvation sites promotes solubilization of Li + containing salts, it is not necessary to substitute every monomer in the polymer design. Rather, optimization of Li + conductivity relies on a balance between imidazole presence and the ability of the chains to rearrange locally to facilitate transport. Lowering the imidazole content in the ethane-imidazole series leads to a 10-fold increase in conductivity, while conductivity decreases for the phenyl-imidazole series due to differences in steric bulk. Normalizing conductivity by T g reveals a threshold ligand density above which increased solvation sites do not improve conductivity, but below which the conduction gradually decreases. NMR spectroscopy shows the high temperature Li + transport number increases slightly with increasing grafting density, from around 0.17 to 0.24. NMR T 1 ρ relaxation reveals that the Li + ions are present in two environments with distinct dynamics within the polymer, matching X-ray scattering and PFG results which suggest ion aggregation exists in these polymers. These results emphasize the importance of local re-arrangements in facilitating ion transport at low solvation site density, confirming the role of dynamic percolation, and suggest that an optimum ligand density exists for improved charge transport.